Intellectual property waiver for covid-19 vaccines will advance global health equity. (3rd August 2021) - Erfani, Parsa; Binagwaho, Agnes; Jalloh, Mohamed Juldeh; Yunus, Muhammad; Farmer, Paul; Kerry, Vanessa
Abstract : Parsa Erfani and colleagues argue that a temporary intellectual property waiver for covid-19 vaccines is vital to increase supply, achieve global herd immunity, and advance global health equity